DIDACTIC SIMULATION GAME AS A MODERN METHOD OF SHAPING CHILDREN'S INTELLECTUAL READINESS FOR SCHOOL (EDUCATION IN THE 21ST CENTURY, 2023)
In the article, intellectual readiness is considered as a prerequisite for the child's integratedreadiness for school education. The didactic simulation game is associated with the upcomingeducational activities and behavior of children, since through imitation certain situations ofinteraction between the teacher and junior schoolchildren, as well as children with each other,potentially contributing to their intellectual development, are simulated.Intellectual readiness of children for school means a certain outlook, a reserve of specificknowledge, an understanding of the main laws, developed curiosity, a desire to learn new things.For the formation of intellectual readiness of children for school, the use of elements ofeducational activity is allowed. The task of teachers in the work on the formation of intellectualreadiness of children for school is to competently organize the educational process, integratingvarious types of children's activities and, accordingly, the forms and techniques in which they arecarried out among themselves.At the heart of the didactic imitation game is an imaginary, specially created situation, whichconsists in the child taking on the role and fulfilling it in an organized gaming environment. Theteaching task of a didactic simulation game is realized using game actions performed by children.Senior preschoolers, in the process of playing various situations close to life, "live" thesesituations, studying them in a specific way in direct action.A didactic simulation game will be an effective method of forming children's intellectualreadiness for school, if:1) forming a rich object-game environment necessary for a variety of game activities;2) the connection of game plots with real life;3) taking into account the gender characteristics of children (both in the aspect of organizinggaming activities and in the aspect of intellectual development).
Keywords: intellectual readiness for school, didactic imitation game, imitation, object-game environment.